Главная

Алгебра 7 класс Ю.Н. Макарычев, Н.Г.Миндюк, К.И.Нешков, С.Б.Суворова

ГДЗ учебник по алгебрее 7 класс Ю.Н. Макарычев, Н.Г.Миндюк, К.И.Нешков, С.Б.Суворова

авторы: , , , .
издательство: "Просвещение" 2013 г.

Раздел:

Номер №499

Упростите выражение:
а)
$-0,6a^3b(-2a^2b^3)^3$
;
б)
$0,8xy^4(-6xy^4)^2$
;
в)
$-a^4b^7(-3ab)^2$
;
г)
$(7x^2y)^2 * (-7y^{11})$
;
д)
$(-ac)^6 * (-2a^2c)^5$
;
е)
$3p^2q * (-\frac{1}{3}p^3q)^2$
.

Решение а

$-0,6a^3b(-2a^2b^3)^3 = -0,6a^3b(-8a^6b^9) = 4,8a^9b^{10}$

Решение б

$0,8xy^4(-6xy^4)^2 = 0,8xy^4(36x^2y^8) = 28,8x^3y^{12}$

Решение в

$-a^4b^7(-3ab)^2 = -a^4b^7(9a^2b^2) = -9a^6b^9$

Решение г

$(7x^2y)^2 * (-7y^{11}) = 49x^4y^2 * (-7y^{11}) = -343x^4y^{13}$

Решение д

$(-ac)^6 * (-2a^2c)^5 = a^6c^6 * (-32a^{10}c^5) = -32a^{16}c^{11}$

Решение е

$3p^2q * (-\frac{1}{3}p^3q)^2 = 3p^2q * (\frac{1}{9}p^6q^2) = \frac{1}{3}p^8q^3$